The Role of Communication in Building Cooperation Between Members of the Islamic Student Association Commissariat of the Faculty of Social Sciences, North Sumatra State Islamic University - Dinda Gita Puspita; Muhammad Hafizh Raihan; Wendy Ilham Pratama; Hasan Sazali Maulana; Andinata Dalimunthe (Penerbit Jurnal Indonesia, 2022)
Indonesia is a democratic country, with the highest authority in the hands of the people having an important role in aspects of state life. Therefore, it is very important for people to know about the life of the nation and state or in other words politics. Without political awareness, the level of public political participation is also low which can have an impact on obstacles to national development. Political awareness can be obtained through several things, one of which is joining organizations, especially for students to join student organizations. Student organizations are divided into two, namely intracampus and extrasemous organizations. Intracampus Student Organizations are student organizations that exist in universities and receive student activity funds from college managers and/or from ministries/institutions. This student organization both intracampus and extracrees has played a positive role in providing students with an understanding of political life. One of them is the extra-general organization of the Islamic Student Association. The Islamic Student Association (HMI) is an extractcoat organization founded in Yogyakarta on February 5, 1947/14 Rabi'ul early 1366 H which was initiated by the Pane